Development of a feedback controller for the Antenna Positioner on the MeerKAT Radio Telescope - Dodia, Irshaad Abdul (Department of Electrical Engineering, 2025)
MeerKAT is South Africa's cutting edge radio telescope, designed, deployed and now operated by the South African Radio Astronomy Observatory (SARAO). The telescope consists of an array of 64 individual 13.5 m diameter fully steerable antennas. This project presents a comprehensive approach to the modelling and design of a feedback control system for a MeerKAT antenna. The project first focuses on modelling of the antenna's mechanical dynamics in its two axes of motion: azimuth and elevation. The modelling approach derives a linear lumped model analytical representation of the antenna dynamics, capturing the effects of coupling compliance which results in (anti-) resonance modes, and the reflection of inertia and friction through the drivetrain gearboxes. Thereafter, using a frequency domain system identification analysis approach, experimental data is used to verify quoted parameters from MeerKAT's design documentation against the analytical model. This leads to a system model defined with parametric uncertainty. Wind disturbance plays a significant role in the pointing performance of the antenna. Therefore, focus is then placed on developing an appropriate wind model to represent the on-site wind characteristics and the relationship to the drive-axis disturbances. Finally, the user requirements are distilled into a set of performance requirements, and using the derived system model and understanding of the disturbance behaviour, a systematic approach to a controller design using the QFT methodology is followed. The designed controllers are evaluated against the actual system performance in simulation, indicating that the telescope's stringent pointing and tracking requirements can be satisfactorily achieved. This project provides a well-documented, systematic control system design that is owned by SARAO and can be implemented to improve the pointing performance of the MeerKAT telescope.